Strategies for sustainable upgrading in global value chains: The Egyptian textile and apparel sector - Jan Grumiller; Werner G. Raza; Hannes Grohs (Austrian Foundation for Development Research (ÖFSE), 2020)
The promotion of sustainable value chains is on the rise in the EU, with important implications for textile and apparel (T&A) products. EU T&A supplier countries and firms will increasingly have to adapt to the new EU value chain and market dynamics. Based on a case study of the Egyptian T&A sector, this policy note argues that the required transformation of the industry will be highly demanding. EU development policy should increase support in order to promote sustainable value chains in the T&A sector in Egypt, but also in other MENA countries with export-oriented T&A sectors
Keywords: 330